The fourth branch : reconstructing the administrative state for the commercial republic - Cook, Brian J., 1954- (Studies in government and public policy., 2021)
"The American commercial republic is in trouble, and the administrative state in its current form is a serious contributor to the difficulties. So argues Brian J. Cook in this argument for rethinking and reconstructing the constitutional design of the United States. Conflicts over the status and reach of government administration are as old as the American republic, born as it was out of protests against the corruption of colonial administration by the Crown's officers. Since then the seemingly mundane matters of day-to-day governmental operations repeatedly have been raised to the level of constitutional debate. Without a monarch to personify tyranny, Americans are more than happy to make 'big government' administration-public organizations and the bureaucrats who operate them the embodiment of their worries, fears, and disaffections. Brian J. Cook argues that what underlies these debates are serious systemic and institutional problems stemming from flaws in the American regime's design that have never been effectively rectified. The rise of the administrative state has been a patchwork effort that has led to a stream of adjustments to cope with stresses and strains, but a systemic problem requires a systemic solution. This book dispenses with the assumption that the Constitution's root structure is inviolable and proposes instead to alter the Constitution's separation-of-powers design to elevate administration to the status of an independent fourth branch"--